Impact of a Restriction in Reimbursement on Proton Pump Inhibitors in Patients with an Increased Risk of Gastric Complications - Flinterman, Linda E.; Hek, Karin; Korevaar, Joke C.; van Dijk, Liset (Frontiers in Public Health, 2018)
Governments have several options to reduce the increasing costs of healthcare, including restrictions for the reimbursement of medicines. Next to the intended effect of reduced costs for medicines, reimbursement restriction can have unintended effects such as patients refraining from their treatment which may lead to health problems and increased use of health care. An example of a reimbursement restriction is the one for proton pump inhibitors (PPIs) that became effective in the Netherlands in January 2012. A major unintended effect of this measure could be the that high-risk patients who start with non-steroidal anti-inflammatory drugs (NSAIDs) or low dose aspirin (aspirin), and who have an increased risk of gastric complications for which they are prescribed PPIs refrain from this PPI treatment. The aim of this study was to evaluate the effect of the reimbursement restriction among high-risk users of NSAIDs or aspirin. Do these patients refrain from their PPI treatment and if so do they have an increased risk of gastric complications? Part of the patients starting with NSAIDs or aspirin have an increased risk of gastric complications due to their age, comorbidities or co-medication. The incidence of PPI use during the two years before the reimbursement restriction (2010 and 2011) and two years after the introduction of the reimbursement restriction was compared for patients on NSAIDs or aspirin with an increased risk of developing gastric complications. Impact of age, sex and social economic status was taken into account. Hospital admissions due to gastric complications were studied over the same period (2010-2013). Data were obtained from a large population-based primary care database and a hospital database. The use of PPIs in patients with an increased risk of gastric complications who started NSAID/aspirin increased from 40% in 2010 to 55% in 2013. No impact was found of age, sex or social economic status. There was no increase in hospital admissions due to gastric complications after the reimbursement restriction. The reimbursement restriction on PPIs was not associated with any detectable unintended effects for patients with an increased risk of gastric complications.